Determinants of Trade Balance in Gulf Cooperation Council (GCC) Member Countries - Khusni, Kholilatul; Sunaryati, Sunaryati (Transpublika Publisher, 2024)
The study aims to analyze the effect of inflation, exchange rate, foreign direct investment, GDP per capita and energy consumption on the trade balance of GCC member countries. Secondary panel data from 2002-2021 from GCC member countries is utilized in this research. The data is sourced from the publications of the World Bank, Trade Map, and OIC Statistics Sesric. The analytical approach employed is the fixed-effects model in panel data regression with a SUR cross-section weighted method. The findings suggest that inflation has a detrimental impact on the trade balance, while the exchange rate, Foreign Capital Receipts, and GDP per capita show a notable positive influence. On the other hand, energy consumption is found to have a positive effect on the trade balance but is not statistically significant.